2007
DOI: 10.1080/10941660701761001
|View full text |Cite
|
Sign up to set email alerts
|

Activity Segmentation of the International Heritage Tourism Market to Taiwan

Abstract: The heritage tourism market has developed from being regarded as a small niche segment to a mainstream market of considerable size. In Taiwan, diversified heritage resources hold considerable appeal to the international tourism market. Little research has been completed on international heritage tourists to Taiwan, so this study utilized Taiwan as a case study and examined international tourists to the destination. It first employed cluster analysis based on activity participation to segment the market and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Further, studies identified different groups of tourists based on their distinct demographic characteristics and satisfaction. In the heritage setting, for example, Yan et al (2007) found that three groups of international heritage tourists to Taiwan not only differed in . What are the triggers of Asian visitor satisfaction and loyalty in the Korean heritage site?, Journal of Retailing andConsumer Services, 47, 195-205.…”
Section: Motivation For Visiting Heritage Sitesmentioning
confidence: 99%
“…Further, studies identified different groups of tourists based on their distinct demographic characteristics and satisfaction. In the heritage setting, for example, Yan et al (2007) found that three groups of international heritage tourists to Taiwan not only differed in . What are the triggers of Asian visitor satisfaction and loyalty in the Korean heritage site?, Journal of Retailing andConsumer Services, 47, 195-205.…”
Section: Motivation For Visiting Heritage Sitesmentioning
confidence: 99%
“…Tourist markets can be segmented or subdivided in many different ways. Geographic location (e.g., , activity (e.g., Yan, So, Morrison, & Sun, 2007), expectation (e.g., Juwaheer, 2006), travel expenditure (e.g., Laesser & Crouch, 2006), life style and social values (e.g., Blamey & Braithwaite, 1997), and motivation (e.g., Li, Huang, & Cai, 2009) are some of the most commonly used segmentation techniques in recent tourism literature. Each segmentation variable has pros and cons.…”
Section: Hsu and Lam Identified The Top Five Barriers That Inhibit Chmentioning
confidence: 99%
“…Lee, Lee and Wicks, 2004;Chang, 2006;Li, Huang and Cai, 2009). Other variables include past experience (Wooten and Norman, 2008), personal values (Hede, Jago and Deery, 2004), satisfaction (Smith, Kyle and Sutton, 2010), activities (Kim et al, 2007;Yan et al, 2007) and demographic characteristics (e.g. Lee, Lee and Wicks, 2004).…”
Section: Segmentation In Events and Festivalsmentioning
confidence: 99%
“…Many of these variables tend to be of the demographic type such as gender, age, education, marital status and income (e.g. Lee, Lee and Wicks, 2004;Li, Huang and Cai, 2009;Yan et al, 2007). A few studies have also looked at psychological variables, such as motivation (e.g.…”
Section: Segmentation In Events and Festivalsmentioning
confidence: 99%
See 1 more Smart Citation